The Effectiveness of a Comprehensive Intervention Model in Managing Anxiety in Emergency Patients - Ultra Madani; Ade Kartika (JURNAL KESMAS DAN GIZI (JKG), 2025)
Anxiety is one of the psychological problems often experienced by patients in the Emergency Department (ED), where this condition can affect comfort, compliance with medical procedures, and hinder the treatment and recovery process. Managing anxiety in emergency patients cannot be done through a single intervention, but requires a comprehensive approach. Comprehensive interventions that combine elements of education, therapeutic communication, distraction therapy, and family support are considered more effective in helping patients manage anxiety while in the ED. Based on this, this study aims to evaluate the effectiveness of a comprehensive intervention model in reducing anxiety levels in emergency patients. The study used a quasi-experimental design with a pre-test and post-test approach and involved 100 emergency patients as samples. Anxiety levels were measured using the Self-Rating Anxiety Scale (SAS), and data analysis was performed using the Wilcoxon Signed Ranks Test. The results showed that before the intervention, most patients (63%) were in the moderate to severe anxiety category, and 15% experienced severe anxiety. After the comprehensive intervention, there was a shift in the distribution of anxiety, with 67% of patients in the mild to moderate anxiety category and 19% in a normal condition. Statistical test results showed a significant difference between anxiety scores before and after the intervention.